Improved dead-time elimination method for three-phase power inverters - Raef Aboelsaud; Ahmed Ibrahim; Alexander G. Garganeev; Ivan V. Aleksandrov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In real inverters' operations, it is essential to insert delay time in the pulses provided to the inverter switches to protect the DC link against the short circuits. From this situation, the dead time phenomenon is introduced that causes undesirable performance and distortion of the output signal. Previously, researchers have proposed various schemes for compensating or eliminating dead-time. In this paper, a new dead-time elimination (DTE) scheme is proposed with a guarantee algorithm to eliminate dead-time and overcome the issues produced at the zero-currents-crossing point (ZCC). This method does not require additional hardware or filters to determine the polarity of the output current, and its principle is very simple to implement. The developed DTE method completely removes the dead-time issues on the magnitude and phase of the output voltage, and avoid the problems which can be induced around the ZCC. The results confirm the effectiveness and safety of this method.